(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
The ever-evolving information technology has a significant impact on many industries, one of which is micro, small, and medium enterprises (MSMEs). Kurnia Laundry is an MSME in Ogan Ilir, still using a manual system in recording transactions, stock management, and customer service, which causes inefficiencies and operational delays. The main purpose of the research focuses on the development of a website-based Point of Sale (POS) system that can optimize Kurnia Laundry’s business operations. This research adopts the Research and Development (R&D) method with a waterfall model approach, which includes the phases of analysis, design, implementation, system testing, and maintenance. The results of the study show that the POS system is able to increase the efficiency of transaction recording, speed up the service process, and provide transparent service information to customers. The implementation of this system also helps business owners monitor business performance in real time, manage customer data, and optimize stock management. Thus, the use of the website as a POS system has a significant impact on increasing the efficiency and competitiveness of laundry MSMEs.